Wheat Cost-Return Budget in North Central Kansas - O'Brien, Daniel M.; Duncan, Stewart R.; Dhuyvetter, Kevin C. (My University, 2014)
This publication provides estimated cost and returns for forward farm planning for wheat in north central Kansas.
MF2158_2014_02
Keywords: MF2158; Crops; Economics; MF